2020
DOI: 10.7717/peerj.8173
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a Takagi–Sugeno-Kang fuzzy model assembly for examination of polyphasic loglinear allometry

Abstract: Background The traditional allometric analysis relies on log- transformation to contemplate linear regression in geometrical space then retransforming to get Huxley’s model of simple allometry. Views assert this induces bias endorsing multi-parameter complex allometry forms and nonlinear regression in arithmetical scales. Defenders of traditional approach deem it necessary since generally organismal growth is essentially multiplicative. Then keeping allometry as originally envisioned by Huxley r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 116 publications
(249 reference statements)
0
6
0
Order By: Relevance
“…In order to validate the present view, we adopted the MCA model of Equation (2), that assimilates necessary complexity through scaling parameters expressed as functions α(x) and β(x) depending on covariate. A particular form of this paradigm was addressed by Bervian et al [77] and its generalization into the form offered here was suggested by Echavarria Heras et al [132]. A formal exploration established this construct as a source model from which conventional models aimed to address curvature in geometrical space [88] could be derived.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In order to validate the present view, we adopted the MCA model of Equation (2), that assimilates necessary complexity through scaling parameters expressed as functions α(x) and β(x) depending on covariate. A particular form of this paradigm was addressed by Bervian et al [77] and its generalization into the form offered here was suggested by Echavarria Heras et al [132]. A formal exploration established this construct as a source model from which conventional models aimed to address curvature in geometrical space [88] could be derived.…”
Section: Discussionmentioning
confidence: 91%
“…The extraordinary approximation capabilities of the TSK fuzzy model [133,134] endow H TSK (x) interpolation of allometric patterns in direct scales irrespective of intrinsic complexity. Moreover, the H TSK (x) arrangement makes it possible to detect break points for transition among allometric phases which is unattainable by MCA-DNLR methods [132].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The idea of a biphasic breakpoint-determined biological scaling conveyed the notion of non-log-linear allometry [ 90 95 ]. Extension of Huxley's original idea of a biphasic scaling led to considering multiple breakpoints which in turn spawned the notion of polyphasic log-linear allometry [ 96 102 ]. Broken-line regression techniques [ 37 , 103 108 ] could deliver identification of breakpoints in polyphasic log-linear allometry schemes.…”
Section: Discussionmentioning
confidence: 99%
“…It needs to be augmented by empirical knowledge of the developmental processes that model parameters are supposed to describe. Further research is required to explore alternative models of allometry [Packard, 2009;Echavarria-Heras et al, 2020] in conjunction with additional empirical knowledge of brain development in fish to construct a model of allometry that is biologically more realistic than the standard model of allometry.…”
Section: Discussionmentioning
confidence: 99%